Millimeter spatial resolution in vivo sodium MRI of the human eye at 7 T using a dedicated radiofrequency transceiver array. Issue 2 (12th January 2018) - Wenz, Daniel; Kuehne, Andre; Huelnhagen, Till; Nagel, Armin M.; Waiczies, Helmar; Weinberger, Oliver; Oezerdem, Celal; Stachs, Oliver; Langner, Soenke; Seeliger, Erdmann; Flemming, Bert; Hodge, Russell; et al.
Abstract : Purpose: The aim of this study was to achieve millimeter spatial resolution sodium in vivo MRI of the human eye at 7 T using a dedicated six‐channel transceiver array. We present a detailed description of the radiofrequency coil design, along with electromagnetic field and specific absorption ratio simulations, data validation, and in vivo application. Methods: Electromagnetic field and specific absorption ratio simulations were performed. Transmit field uniformity was optimized by using a multi‐objective genetic algorithm. Transmit field mapping was conducted using a phase‐sensitive method. An in vivo feasibility study was carried out with 3‐dimensional density‐adapted projection reconstruction imaging technique. Results: Measured transmit field distribution agrees well with the one obtained from simulations. The specific absorption ratio simulations confirm that the radiofrequency coil is safe for clinical use. Our radiofrequency coil is light and conforms to an average human head. High spatial resolution (nominal 1.4 and 1.0 mm isotropic) sodium in vivo images of the human eye were acquired within scan times suitable for clinical applications (∼ 10 min). Conclusions: Three most important eye compartments in the context of sodium physiology were clearly delineated in all of the images: the vitreous humor, the aqueous humor, and the lens. Our results provide encouragement for further clinical studies. The implications for research into eye diseases including ocular melanoma, cataract, and glaucoma are discussed. Magn Reson Med 80:672–684, 2018. © 2018 International Society for Magnetic Resonance in Medicine.